Effects of non-isothermal single circular impinging jet on a quasi-adiabatic flat plate - Mohd Saiah, Helmey Ramdhaney (2011)
A test facility for the jet impingement cooling technique was redesigned based on literatures to investigate the effect of varying jet impingement hole diameter and jet impingement Reynolds number to the flow thermal behaviour. The total hydraulic diameter of the facility, inlet nozzle and the orifice plates were designed in accordance to the British Standards for fluid flow in a closed conduit, BS1042. Jet impingement test plates were fabricated by scaled factors to represent the real condition in the turbine blade itself. The experimental tests include single jet impingement hole arrangements with hole diameter of 5, 7, and 10 mm, and jet impingement Reynolds number ranging from 20000 - 30000. Video images of the experiment were captured using a digital video camera, and the video images were then extracted into still images. These still images were analyzed using MatLab software to get the heat transfer coefficient and surface temperature. The most suitable design parameters at a given range of design parameters were pointed out. The experimental data obtained includes the effects of varying the jet impingement hole diameter and the jet impingement Reynolds number on heat transfer coefficient distribution and the non-dimensional parameter, Nusselt number. The coverage area of the stagnation region and the location of the wall jet region were also considered. It was found that increasing jet impingement hole diameter resulted in an increase towards the stagnation region area and wall jet region location. Development of jet impingement potential core was also discussed and optimal design parameters for the current test facility were pointed out. At jet impingement Reynolds number of 20000, the 5 mm jet impingement hole diameter design achieved the highest heat transfer process, but as the jet impingement Reynolds number increased to 25000 and 30000, the 10 mm jet impingement hole diameter dominated the heat transfer process. Recommendation on future work would include the integration of turbine stage internal cooling technique and external cooling technique and also the utilization of multiple thermochromic liquid crystals coating for a better heat transfer coefficient distribution.